Regulatory burden and business dynamics: a preliminary analysis. Issue 3 (13th August 2018) - Clark, J.R.; Nesbit, Todd
Abstract : Purpose: Stigler (1971) first presented a theory of regulation in which the regulator eventually serves the interests of the regulated rather than in the interest of the public good. In such an institutional environment, one should expect to observe outcomes associated with reduced competitive pressures on existing firms. The paper aims to discuss this issue. Design/methodology/approach: In this paper, the authors use RegData, which quantifies regulatory restrictions by industry, to determine whether and to what degree regulation reduces establishment entry and the associated job creation and how regulation impacts existing establishment exit and job creation and destruction. Findings: The results, while not definitive, are supportive of Stigler's theory of regulatory capture. Originality/value: This paper adds to the small but growing empirical literature examining the effects of cronyism more broadly. Prior studies of regulation have generally been either narrowly focused on a specific regulation or employ less precise measures of the extent of regulation. By employing RegData as a measure of regulatory restrictions by industry, this paper offers new insights on the impact of regulation on business dynamics.